Evaluation of Indonesian and two types of Japanese honey on the acceleration of cutaneous wound healing: an experimental study in mice - Haryanto Haryanto; Kanae Mukai; Nakajima Yukari; Mayumi Okuwa; Cau Kim Jiu; Junko Sugama; Toshio Nakatani (Journal of Health Technology Assessment in Midwifery, 2019)
The purpose of this study is to evaluate and clarify the effect of Indonesian honey, two types of Japanese honey and hydrocolloid dressing on wound healing process. Four groups of male mice were treated to produce two circular full-thickness skin wounds on the dorsum. They were then randomly allocated to receive daily Indonesian honey, Japanese honey (Buckwheat and Acacia honey) or hydrocolloid dressing as a control for treatment application. Macroscopic findings were observed from day 0 to 14 after wounding. Microscopic evaluation was assessed using qualitative analysis. The ratios of wound areas for honey groups on day 3 and 7 were smaller than those of the control group. Wound areas of honey groups gradually decreased to almost the same wound area as the control group on day 14, while the wound area of the control group peaked on day 5 and rapidly decreased until day 14. Microscopic finding that Indonesian honey was different with Japanese honey especially Buckwheat honey.